2003
DOI: 10.1001/archfaci.5.1.53
|View full text |Cite
|
Sign up to set email alerts
|

A Compositional Analysis of Human Nasal Septal Cartilage

Abstract: Background: Nasal septal cartilage is well established as an autograft material. Tissue engineering methods are now being developed to synthesize cartilage constructs with the properties of this type of cartilage. However, important baseline data on the composition of native septal cartilage is sparse.Objectives: To characterize quantitatively the major biochemical constituents of native adult human septal cartilage and determine age-or sex-related variation in composition.Methods: Cartilage was harvested from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 20 publications
2
87
1
3
Order By: Relevance
“…This raised the question of whether this difference is unique to the endplate or common to all hyaline cartilages. Recent evidence was presented indicating that human nasal septal cartilage from young (33.7±3.9 years), middle-aged (50.2±5.4 years) and aged (73.5±5.8 years) adults had GAG/hydroxyproline ratios of 3.5, 3.3 and 2.5, respectively (Homicz et al, 2003). Similarly, others have found that in subjects aged 14 to 45 years the GAG/ hydroxyproline ratio in talar ankle cartilage, distal femur knee cartilage, and tibial plateau knee cartilage is 1.8, 1.3 and 1.3, respectively (Treppo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raised the question of whether this difference is unique to the endplate or common to all hyaline cartilages. Recent evidence was presented indicating that human nasal septal cartilage from young (33.7±3.9 years), middle-aged (50.2±5.4 years) and aged (73.5±5.8 years) adults had GAG/hydroxyproline ratios of 3.5, 3.3 and 2.5, respectively (Homicz et al, 2003). Similarly, others have found that in subjects aged 14 to 45 years the GAG/ hydroxyproline ratio in talar ankle cartilage, distal femur knee cartilage, and tibial plateau knee cartilage is 1.8, 1.3 and 1.3, respectively (Treppo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As with articular cartilage, the discs are thought to resist compressive forces by their high content of the proteoglycan aggrecan in the NP (Hutton et al, 2000). In addition, both tissues also contain proteoglycans that have the ability to interact specifically with collagen molecules (Adams et al, 1977;Hayes et al, 2001;Sztrolovics et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Calf thymus DNA served as a standard (Invitrogen). The native tissue specimens, decellularized cell-derived ECM, and scaffolds seeded for 14 days with hBM-MSCs or hIVDCs were digested with proteinase K (Sigma-Aldrich) solution (10 mg/ml dissolved in 50 m M Tris/HCl, 1 m M EDTA, 0.5% Tween 20, pH 8.5) for 16 h at 55 ° C. Thirty minutes of centrifugation at 10,000 g followed and the supernatant was stored at 4 ° C. Based on the assumption that each cell contains roughly 7.7 pg DNA [Homicz et al, 2003], the semiquantitative cell nuclear content of the samples was estimated. GAG contents were assessed by standard DMMB assay [Farndale et al, 1986].…”
Section: Total Dna and Gag Contentmentioning
confidence: 99%
“…The calculated refractive index is 1.42 + 0.02, smaller than that of the other samples studied. The elastic constants c 33 and c 11 were derived from the spectra at u ¼ 08 and 908, as before, using the density of wet articular cartilage [41], 1.1 g cm 23 (table 1).…”
Section: Nuchal Ligamentmentioning
confidence: 99%